Determining the optimal age of breeding gilts and its impact on lifetime performance, Literature review - Joab, Malanda (Acta Agraria Debreceniensis, 2019)
Lifetime sow performance is a critical indicator for producers managing a commercial sow herd. It is comprised of sow longevity, lifetime piglets born alive, lifetime number of pigs weaned and lifetime non-productive sow days. Increased lifetime performance and longevity in sows reduces costs of replacement gilts and improves herd performance and profitability (Sasaki et al., 2008, 2011). One of the most critical factors driving the performance of sow herds is gilt management. Decisions regarding gilts have profound effects on sows’ lifetime performance. Age at first breeding of a gilt is a management decision that has been shown to affect performance and retention of the gilt in a herd.The main aim of this review is to establish factors affecting age of first breeding of gilts and its impact on lifetime performance.